The influence peddling crime and the treatment of the “judicial or administrative proceedings” element - Chanjan Documet, Rafael (2020)
This article addresses an approximation to the influence peddling crime’s elements, especially of the judicial or administrative proceedings. About the latter, it explains the limitation that it imposes because it restricts the scope of application of this crime, thus generating situations of impunity in many cases. In this vein, a modification of this crime it be proposed within the framework of an adequate criminal anti-corruption policy, following the international legal instruments binding on Peru in this area. So, the influence peddling crime should be applied to public matters in general and not only to a case qualified as judicial or administrative; what is relevant should be that these are procedures in which a public officer decides on a matter with discretionary powers.